2014
DOI: 10.1007/s13142-014-0253-4
|View full text |Cite
|
Sign up to set email alerts
|

Dulce Mothers: an intervention to reduce diabetes and cardiovascular risk in Latinas after gestational diabetes

Abstract: Latina women with prior gestational diabetes mellitus (GDM) are at elevated risk for type 2 diabetes mellitus and cardiovascular disease. Few primary prevention programs are designed for low socioeconomic status, Spanish-speaking populations. We examined the effectiveness of a Diabetes Prevention Program (DPP) translation in low-income Latinas with a history of GDM. Eighty-four Latinas, 18-45 years old with GDM in the past 3 years, underwent an 8-week peer-educator-led group intervention, with tailoring for La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(92 citation statements)
references
References 51 publications
3
88
0
1
Order By: Relevance
“…Such barriers could make it difficult for women to participate in intensive, group-based classes such as offered under the Diabetes Prevention Program. Prior studies have described low uptake and adherence in class-based interventions among this population [42,43]. In contrast, interventions that could be done during flexible hours within the home (e.g., delivered via the internet) may have higher uptake among women with GDM.…”
Section: Discussionmentioning
confidence: 91%
“…Such barriers could make it difficult for women to participate in intensive, group-based classes such as offered under the Diabetes Prevention Program. Prior studies have described low uptake and adherence in class-based interventions among this population [42,43]. In contrast, interventions that could be done during flexible hours within the home (e.g., delivered via the internet) may have higher uptake among women with GDM.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies employed study-specific items measuring dietary behavior, or did not report details of measures used. Four studies reported reduction in dietary fat intake, 16,18,24,25 two reported reduction in sugar consumption/glycemic load, 16,22 and three reported increases in consumed fruit and vegetable servings. 15,16,22,25,26 Given the inconsistency of constructs measured and heterogeneity in measurement method and timeline, effect sizes could not be calculated for these outcomes.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…In fact, it is unclear whether any single measurement of diet or physical activity was utilized across more than one study. Seven studies examined changes in physical activity, all measured by participant self-report, 15,18,2124,26 with some utilizing validated, reliable measures for Hispanic populations (e.g., Global Physical Activity Questionnaire, International Physical Activity Questionnaire, Rapid Assessment of Physical Activity) and others employing study-specific individual physical activity items. Four studies reported significant changes in physical activity levels post-intervention 15,18,23,26 (Appendix Table 1).…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations